Case report: Rapid recovery after intrathecal rituximab administration in refractory anti-NMDA receptor encephalitis: report of two cases - Reda, Mahasen; Jabbour, Rosette; Haydar, Asad; Jaafar, Fatima; El Ayoubi, Nabil; Nawfal, Omar; Beydoun, Ahmad (Frontiers in Immunology, 2024)
Background: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is one of the most prevalent etiologies of autoimmune encephalitis. Approximately 25% of anti-NMDAR encephalitis cases prove refractory to both first and second-line treatments, posing a therapeutic dilemma due to the scarcity of evidence-based data for informed decision-making. Intravenous rituximab is commonly administered as a second-line agent; however, the efficacy of its intrathecal administration has rarely been reported. Case summary: We report two cases of severe anti-NMDAR encephalitis refractory to conventional therapies. These patients presented with acute onset psychosis progressing to a fulminant picture of encephalitis manifesting with seizures, dyskinesia, and dysautonomia refractory to early initiation of first and second-line therapeutic agents. Both patients received 25 mg of rituximab administered intrathecally, repeated weekly for a total of four doses, with no reported adverse effects. Improvement began 2-3 days after the first intrathecal administration, leading to a dramatic recovery in clinical status and functional performance. At the last follow-up of 6 months, both patients remain in remission without the need for maintenance immunosuppression. Conclusion: Our cases provide evidence supporting the intrathecal administration of rituximab as a therapeutic option for patients with refractory anti-NMDAR encephalitis. Considering the limited penetration of intravenous rituximab into the central nervous system, a plausible argument can be made favoring intrathecal administration as the preferred route or the simultaneous administration of intravenous and intrathecal rituximab. This proposition warrants thorough investigation in subsequent clinical trials.